Marine diatoms are a rich source of bioactivity - Ingebrigtsen, Richard Andre (Norske havforeres forening, 2014)
As part of the MabCent-SFI drug-discovery initiative organized by the University of Tromsø, the coastal areas of northern Norway and the Barents Sea have been investigated (2006-2014). We saw that bioac- tive compounds from diatoms are very rarely reported (1-4). There- fore we desided that during the initial MabCent research cruises, di- atom strains should be isolated and kept in a culture collection and subsequently mass-cultivated in order to investigate their bioactivity by screening the diatom extracts using the Marbio (UiT) assay line.